Pelaksanaan Pengelolaan Sampah Plastik di Sungai Bengawan Solo oleh Dinas Lingkungan Hidup Kota Surakarta - Baharrudy Isa Aulia; Pius Triwahyudi (Jurnal Discretie, 2020)
This study aims to determine the implementation of plastic waste management in the Solo River by the Surakarta City Environment Agency. This type of legal research is non-doctrinal or empirical. It is descriptive, with a qualitative approach stated by respondents in writing or verbally and real behavior. The way to collect legal material through field research is observation, interview, documentation and literature study using primary and secondary law data. Qualitative analysis, from the reduction of data and presentation of data that is linked so that conclusions can be drawn. Conclusion of the results of the discussion in response to the problem of this study, the Surakarta City Environmental Agency has made several efforts in the management of plastic waste in the Bengawan Solo River as an effort to conserve the river from garbage pollution and the implementation of the management of plastic waste which is carried out through several work programs including the establishment of river working groups , the formation of labor-intensive and outreach to the people of the City of Surakarta.